IMPROVEMENT OF TRADITIONAL ESR PERFORMANCE FOR RAPID DETECTION OF FREE RADICALS IN MATERIALS - Didik R Santoso; Chomsin S Widodo; Unggul P Juswono (Journal of Environmental Engineering and Sustainable Technology, 2017)
To detect the presence of free radicals in materials, a traditional Electron Spin Resonance (ESR) requires repeating setting values of the external magnetic field (B0)  as well as the frequency of microwave signal (u) to achieve resonance conditions, and it must be conducted manually. The procedure requires considerable time, so that become ineffective. In this paper, we propose a simple technique to improve the functionality of the traditional ESR by implementation of ramp-type magnetic field and high-speed data acquisition system. In here, we generate ramp-type voltage signal based on PIC16F876 microcontroller as the main device. This signal is converted to the current source by using the circuit of V to I converter, then injected to the Helmholtz coil to generate a ramp-type magnetic field. Some experiments are carried out in order to make validation and determine the performance of the developed system. By the technique, the traditional ESR becomes an automatic ESR-spectrometer and has the capability to identify some kinds of free radicals faster.Keywords: ESR, free-radical, ramp-B.